Relationship Management: a sales role, or a state of mind? An investigation of functions and attitudes across a business-to-business sales force - Davies, Iain A.; Ryals, Lynette; Holt, Sue (Elsevier Science B.V., Amsterdam., 2010)
Commentators suggest that the business-to-business sales role is changing and evolving into relationship management. Previous research indicates that a relationship management role is very different from ‘traditional' sales, and that it may require a different attitude on the part of the relationship manager. This research explores attitudes towards various aspects of relationship management across an entire international business-to-business sales force in a service industry context. We find that attitudes towards relationship management do not in fact align with job role. A cluster analysis reveals three attitudinal types of sales person: Self-Directed; Team Leaders; and Strategic Sellers. Our findings suggest that some individuals may have attitudes that are inappropriate to their roles, and that attitudes should be taken into account when selecting relationship manager